ya' between vocative and non-vocative use in Egyptian film language - Henen, David (AUC Knowledge Fountain, 2019)

(untitled)
This study investigates the functional and formal features of constructions built with the particle ya in the Egyptian Arabic film language of the film eš-šabaḥ (The Ghost) (2007). Studying ya is of interest as it is the most frequent lexical item after the conjunction we (and) in the data. By means of using WordSmith Tools Lexical Analysis Software, a concordance of instances of ya in the data was built. In line with the Speech Act theory by Austin (1975), a quantitative design was employed which enabled the findings to be classified according to their functional and formal properties. Regarding formal features, the results show specific patterns and collocates within each functional category of ya. As regards functional features, 88% of the ya phrases in the data convey vocative use while 12 % indicate non-vocative use. Within the vocative use, ya phrases are found to be mainly identificational, activational, predicational, or unreal. There is a category for contractures with an omitted vocative head. In non-vocative use, ya is found as an exclamation particle. This study has implications for teaching EA, formulating the grammar rules of EA, and translating dialogs from and into EA.